The impact of the HIV epidemic on length of stay in an Acute Psychiatric ward at a general hospital in Gauteng - O’Brien, Sharne (My University, 2021)
Acute inpatient psychiatric services in South Africa are under pressure, as evidenced by high bed-occupancy rates.1 2 Several factors may contribute to this situation, including the policy of deinstitutionalisation, together with a lack of sufficient community mental health services. Another possible factor contributing to a longer length of stay in hospital is the admission of patients with complex conditions, including medical comorbidity. The HIV epidemic in South Africa was predicted to impact on psychiatric services due to the prevalence of neuropsychiatric complications in HIV-infected individuals. This study aimed to determine whether patients with a comorbid HIV infection admitted to the acute psychiatric unit in a Southern Gauteng general hospital had a longer length of stay compared to patients who were HIV-seronegative. This study was a retrospective record review of all patients admitted to and discharged from the acute psychiatric unit between the 1st of January and the 31st of December 2016. The patient’s demographic and clinical profile is described in this report. Additionally, the association between HIV-serostatus and the presence of any medical comorbidity and length of stay is analysed. An important finding of this study was that 43% of patients admitted to the unit had unknown HIV-serostatus, suggesting that patients are not routinely tested for HIV during their admission. Patients with a longer length of stay were more likely to be tested for HIV. Of the 295 patients whose HIV status was known, 20.3% were HIV positive. This is similar to national prevalence figures. There was no significant difference in length of stay between those patients who were HIV positive compared to those who were HIV negative. Therefore, the primary hypothesis of this study was not proved. The record review found that 24.3% of patients had a medical comorbidity that required clinical attention. Almost half of this was due to HIV infection, with cardiovascular diseases following at 5%. This is in contrast to the higher prevalence of comorbid medical conditions in acute psychiatric inpatient populations found internationally. 71 72 In these studies, which primarily emanate from high-income countries, cardiovascular diseases are the most common comorbid medical condition. The results of this study suggest that there may be inadequate screening for HIV and other medical comorbidities in psychiatric patients admitted to this unit. Substance use was seen amongst 64% of this study population. A large proportion of these were not tested for HIV, most likely due to shorter admissions. This is most concerning given the bidirectional relationship in causality between HIV infection and substance use.3 It is recommended that more attention is paid to screening all patients for HIV infection who are admitted to an acute psychiatric unit. The opt-out approach to HIV counselling and testing has been recommended for this population,4 with due attention to an ethical approach to consent for such testing. Clinicians at all levels of health care should also be reminded to screen psychiatric patients for all medical conditions, however, in the midst of the current HIV epidemic in South Africa it is vital that at any point at which a patient has contact with psychiatric services opt out testing for HIV be routinely offered
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Psychiatry, 2021